2019
DOI: 10.1088/1748-9326/ab1abf
|View full text |Cite
|
Sign up to set email alerts
|

Even for the environment, context matters! States, households, and residential energy consumption

Abstract: This study adopts a multi-level approach to examine the extent to which state-and household-level factors shape residential energy consumption in the United States, focusing on efficiency improvement and affluence. Analyzing the 2009 Residential Energy Consumption Survey, state-level energy efficiency data from the American Council for an Energy-Efficient Economy (ACEEE), and other sources, we find that state context significantly influences energy consumption at the household level. Households in states scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…11 Adua and Clark revealed mixed relationships between investment in energy efficiency technologies and residential energy consumption, as some measures of efficiency technology are negatively related to residential energy consumption, while others are positively related to it. 12 Achour and Belloumi indicated that the overall effect of economic output, transportation intensity, population scale, and transportation structure on energy consumption is positive, whereas the overall effect of energy intensity is negative. It was shown that energy intensity played the dominant role in decreasing energy consumption during the study period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Adua and Clark revealed mixed relationships between investment in energy efficiency technologies and residential energy consumption, as some measures of efficiency technology are negatively related to residential energy consumption, while others are positively related to it. 12 Achour and Belloumi indicated that the overall effect of economic output, transportation intensity, population scale, and transportation structure on energy consumption is positive, whereas the overall effect of energy intensity is negative. It was shown that energy intensity played the dominant role in decreasing energy consumption during the study period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quantitative research at the sub-national level also presents challenges for the general propositions of ecological modernization theory (Adua and Clark 2019, Adua et al 2016, Lutzenhiser and Hackett 1993. For instance, Adua et al (2016) find that household income, analogous to national income per capita, drives higher CO 2 emissions from residential energy consumption in the United States.…”
Section: Empirical Evaluations Of Ecological Modernizationmentioning
confidence: 99%
“…Prior quantitative analyses of ecological modernization arguments focus on (1) how economic development (usually measured as GDP per capita) and other indicators of modernity are directly related to specific environmental outcomes (e.g., Jorgenson 2006, Jorgenson and Clark 2012, Thombs 2018, Thombs and Huang 2019, York et al 2003a, 2004, or (2) the impacts of efficiency improvement on environmental quality (Adua 2010, Adua and Clark 2019, Adua, York, and Schuelke-Leech 2016, Goklany 2009, Grant, Jorgenson, and Longhofer 2020. While assessing these direct relationships is important, the ecological modernization perspective proposes that economic development facilitates several intermediate mechanisms by the state, corporate entities, and civil society that lead to reductions in environmental harms.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid disasters cause mass displacement, while ongoing climatic changes lead to economic migration that is intended to be temporary but often becomes permanent (Van Praag & Timmerman 2019). This phenomenon is playing out in the Sahel region of Africa, where climate-related changes have left nearly 7 million people food insecure and more than 2.5 million people have already been displaced (Adepoju 2019). While historical analyses of push and pull factors in climate migration can give insight into future migration strategies (Whitley et al 2018a), analyses must also engage inequalities and intersectional identities.…”
Section: Climate Change and Disabilitymentioning
confidence: 99%